(untitled) (SCIENCE TIME JOURNAL, 2026)
This present article kind of examines the theoretical bases of gender as this linguistic thing, you know, especially how it links grammar with the social stuff, within universal linguistics. The results add to a bigger understanding about how language does encode and keeps going, and sometimes even gently resists social hierarchies tied to gender.